CUSTOMERS’ ASSESSMENT ON E- BANKING SERVICE QUALITY IN BANGLADESH: CHALLENGES AND STRATEGIES - Barua, Dhiman; Akber, S. M. (American Finance & Banking Review, 2021)
This paper attempts to investigate to understand customers’ evaluation regarding service quality of e-banking in Bangladesh. It also examines the major challenges and required strategies for promoting e-banking. To conduct the study, a total number of 205 respondents were taken as sample from Chittagong region by using simple judgmental sampling technique. A face-to-face interview method was followed by using a structured questionnaire to collect the data. Five points Likert scale was used to examine the customers’ evaluation on the service quality and through statistical measures it analyze the problem. Garret’s ranking technique was applied to rank the qualitative data for analyzing challenges and required strategies of e-banking. The study reveals that from the customers’ assessment, e-banking saves time and hazard, facilitates quick and easier access to information, speedy transaction, receiving service easily, ensures accuracy, effectiveness and security, provides versatile service, anytime, anywhere banking facility. The study also found that technological disturbance, insufficient infrastructure, unavailability of service in rural areas, high service charge are the major challenges of e-banking service in Bangladesh. The customers suggests to develop infrastructure, upgrade technology, increase security measure, enhance promotion for developing customers’ awareness, introduce innovative initiative of Bangladesh bank, extend service across the country etc. JEL Classification Codes: G21, L15.